Laparoscopic surgery for lower biliary tract carcinoma (carcinomas of the inferior bile duct and duodenal papilla) - Kurata, Masanao; Kobayashi, Shin; Kamisawa, Terumi; Honda, Goro; Okuda, Yukihiro; Sakamoto, Katsunori (Tando, 2014)
In surgery for carcinoma of the lower biliary tract, pancreaticoduodenectomy, bypass, and transduodenal papillectomy are performed via a laparoscopic approach. The current status of these surgeries is summarized referring to literature in Japan and other countries. Laparoscopic pancreaticoduodenectomy is increasingly being performed, and relatively favorable outcomes in many cases have been reported in other countries. This surgery may become widespread in the future as a procedure beneficial for patients because of its low invasiveness, but investigation of its feasibility with regard to curability, such as level-2 lymph node dissection and the range of bile duct resection often discussed in Japan, has been insufficient. On the other hand, laparoscopic surgery is more difficult than open surgery, and the operative time is likely to be longer. Since the feasibility of the technique can be increased by simplification, to generalize laparoscopic pancreaticoduodenectomy safely, it is necessary to identify the feasible range compatible for both techniques and surgical oncology.